2022
DOI: 10.1007/s41207-022-00307-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19 future trends for different European countries using Pearson correlation

Abstract: The ability to accurately forecast the number of COVID-19 cases and future case trends would certainly assist governments and various organisations in strategising and preparing for the newly infected cases well in advance. Many predictions have failed to foresee future COVID-19 cases due to the lack of reliable data; however, such data are now widely available for predicting future trends in COVID-19 after more than one and a half years of the pandemic. Also, various countries are closely monitoring other cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Pearson correlation is used to assess a possible association between two continuous variables (Muhaidat et al. 2022 ). In this study, Pearson correlations indicated that the pharmacodynamic effects of DBD could correlate with the biological function of β-OHB by inhibiting HDAC1 activity and resisting oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson correlation is used to assess a possible association between two continuous variables (Muhaidat et al. 2022 ). In this study, Pearson correlations indicated that the pharmacodynamic effects of DBD could correlate with the biological function of β-OHB by inhibiting HDAC1 activity and resisting oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the empirical part of the research, we focused more closely on evaluating the impact of the covid-19 pandemic on the performance of SMEs by calculating the correlation through the Pearson coefficient. This method of determining intercorrelation is most commonly used for numerical variables and does not take into account the dependence of the variables, but treats them as equivalent (Muhaidat et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Through extensive simulation we attempted to identify a scaling factor, F to adjust the values of M (i.e., our contact matrix) to match the official cases. For the case when there is no lockdown, we finally adopted F = 1 6 and to calibrate for different degrees of lockdown (as well as to simulate the effect of different variants), we used the following range: 1 12 ≤ F ≤ 1 9 .…”
Section: Calibration Of Abm-sdmentioning
confidence: 99%
“…This is however, challenging as, arguably, due to various (non-)epidemiological and other parameters, COVID-19 spread has taken different pathways in different regions. Some of these pathways or pandemic trends are correlated while they can also have no similarity at all [1].…”
Section: Introductionmentioning
confidence: 99%